Safety of a 2-dose primary series of 13-valent pneumococcal conjugate vaccine in Indonesian infants (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND In 2017, the Indonesian Technical Advisory Group on Immunization recommended a safety monitoring demonstration program for the 13-valent pneumococcal conjugate vaccine (PCV13) in West Lombok and East Lombok, West Nusa Tenggara to evaluate the 2-dose primary series (2 and 3 months of age) for serious adverse events (SAEs), adverse events, systemic events, and local reactions. METHODS A total of 1,083 infants from 10 primary healthcare centers were analyzed, with 687 receiving the first dose and 396 receiving the second dose. Based on the national immunization program, they received PCV13 + DTwP-HB-Hib + OPV (n = 544), PCV13 + DTwP-HB-Hib (n = 101), or PCV13 only (n = 403). They were monitored for 30 min after vaccination for any immediate SAEs, and parents were given a diary card to record safety information prospectively for 28 days. RESULTS No immediate SAEs were observed, and no SAEs were reported during 28 days after vaccination. Reports of local reactions and systemic events predominated on days 1–3 post-vaccination. Severe fever (axillary temperature >39.0°C) was uncommon (<2% of all infants). Most irritability was mild to moderate. Local pain was more frequent after the first dose than after the second dose. It was distributed evenly across mild, moderate, and severe classifications, while redness and swelling were mostly mild to moderate. CONCLUSIONS The PCV13 primary series demonstration program in Indonesia confirmed tolerable local and systemic reactions.